Science Video Media as an Effective Tool to Enhance Self-Awareness, Responsibility, and Prosocial Behavior in Early Childhood - Dwi Rulismi; Rika Partika Sari; Syisva Nurwita; Ranny Fitria Imran; Masterjon Masterjon (Utan Kayu Publishing, 2025)
This study aims to measure the effectiveness of science video media in enhancing the social-emotional abilities of early childhood learners, covering aspects such as self-awareness, a sense of responsibility, and prosocial behavior. The research employed a quantitative approach using a quasi-experimental design, involving 18 children aged 5–6 years, divided into an experimental group and a control group. The research instruments consisted of observation sheets, questionnaires, and teacher interview guides. Data analysis was conducted quantitatively using an independent t-test, complemented by qualitative analysis to provide a deeper understanding of the video media's effectiveness. The findings reveal that the use of science video media significantly improved all three social-emotional aspects. Children became more capable of recognizing and understanding themselves, demonstrated increased responsibility toward themselves and others, and showed more active prosocial behavior, such as cooperation and empathy. Science video media proved to be effective in helping children understand social and emotional values through engaging visual and narrative approaches. By presenting real-life situations and relatable characters, the children experienced more practical and contextual learning. These results reinforce social learning theory, which emphasizes the importance of observation and imitation in children's learning processes. Video media allows children to imitate positive behaviors portrayed in the content, thereby naturally shaping their character and social skills. Thus, science video media can serve as an innovative and effective educational tool to support the social-emotional development of young children. This media can be integrated into the learning process both at school and at home as part of an educational strategy that is responsive to children's needs in the digital era.